Itchy, Itchy Chickenpox - Maccarone, Grace; Lewin, Betsy (New York : Scholastic Inc., 1992)
Peppy rhymes present the humorous side to a common ailment.
"Level 1."
Keywords: Chickenpox -- Fiction; Stories in rhyme